Therapy through limited language - Rathna N (Journal of All India Institute of Speech and Hearing, 1970)
The field of Speech and Hearing is growing up in India and it is becoming increasingly clean that the discipline has to grow its roots into this soil. It has to take its nourishment from the soil in which it is rooted and it has to adapt itself to meet the needs peculiar to this country. It is common knowledge that India provides many unique challenges and thus demands approaches which are not fully imported from other climates. We can ill afford to limit ourselves attempting research for international consumption ignoring the real challenges of our own nation. Tropicalisation and import substitution is the order of the day and this must hold true in professional activities.